2023
DOI: 10.1002/nop2.1588
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding the retention of nurses: A systematic review on determinants of nurse's intentions to stay

Abstract: Aim To explore factors that influence registered nurses' intention to stay working in the healthcare sector. Design A systematic review and narrative synthesis. Methods CINAHL, Medline and Cochrane library databases were searched from Jan 2010 to Jan 2022 inclusive and research selected using a structured criterion, quality appraisal and data extraction and synthesis were guided by Campbell's Synthesis Without Meta‐analysis. Results Thirty‐four studies identified that nurses stay if they have job satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…The COVID-19 pandemic posed unprecedented challenges for the healthcare sector, especially for ICUs, which experienced dramatic increases in nurse turnover because of the increase in workload, stress, and burnout 18. Current literature describes several factors that influence nurse retention, such as organizational culture, leadership style, professional development, and peer support 2,4,7,18. This project contributes to the literature by demonstrating the feasibility and effectiveness of a collaborative and comprehensive onboarding and orientation process for new hires.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The COVID-19 pandemic posed unprecedented challenges for the healthcare sector, especially for ICUs, which experienced dramatic increases in nurse turnover because of the increase in workload, stress, and burnout 18. Current literature describes several factors that influence nurse retention, such as organizational culture, leadership style, professional development, and peer support 2,4,7,18. This project contributes to the literature by demonstrating the feasibility and effectiveness of a collaborative and comprehensive onboarding and orientation process for new hires.…”
Section: Discussionmentioning
confidence: 95%
“…18 Current literature describes several factors that influence nurse retention, such as organizational culture, leadership style, professional development, and peer support. 2,4,7,18 This project contributes to the literature by demonstrating the feasibility and effectiveness of a collaborative and comprehensive onboarding and orientation process for new hires. Future studies should investigate the transferability and scalability of…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to other studies that have shown that younger workers, combined with less years' experience, were more likely to think about the likelihood of being called compared to older adults. 48 Additionally, there is a 'survivor' bias amongst shift workers, 50,51 with workers who cannot cope with shift work typically not continuing in the profession. Therefore, those that continue are usually older, more experienced and have been able to adapt to working shift work and managing on-call schedules.…”
Section: Discussionmentioning
confidence: 99%